Flood risk zoning in Torbat-e Heydarieh city using by fuzzy logic - Sanaz Saeedi; Mehdi Asiaei; Fatemeh Goharkhah (جغرافیا و توسعه, 2022)
The aim of this study was to zoning the risk of floods in Torbat Heydariyeh with emphasis on urban and rural areas in2020.This research is an applied type in which fuzzy logic,analytical hierarchy system and gratitude information system have been used.In this study, slope,distance from river,elevation,geology,landuse,precipitation, drainage density and vegetation were investigated.It should be noted that in order zoning the risk of flood occurrence in Torbat Heydariyeh,based on the above criteria,first the layers in Arc GIS environment have been converted and then using fuzzy,fuzzy membership functions and finally fuzzy maps of the layers have been obtained.Then,with the help of EXCEL software,the AHP process was performed and then the final weight of the criteria was combined with fuzzy layers and finally the obtained maps were matched with fuzzy operators and the zoning map was extracted.The results show that the main variables affecting flooding in the study area are slope variables with a weight coefficient of 0.306and precipitation with a weight coefficient of 0.175.Of course,vegetation variable with a weight coefficient of 0.040has the least effect on the study area.Therefore,it can be concluded that Torbat Heydariyeh is very high risk according to the classification map of flood risk in the region,so more attention should be paid to watershed management operations in the city.It should also be noted that the Torbat Heydariyeh is located in very low risk area and in terms of rural settlements,most of the villages of this city are located in the area with very low and high risk of vulnerability.